2011
DOI: 10.1152/ajplung.00368.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fas/FasL system in a model of RSV infection in mechanically ventilated mice

Abstract: Infection with respiratory syncytial virus (RSV) in children can progress to respiratory distress and acute lung injury necessitating mechanical ventilation (MV). MV enhances apoptosis and inflammation in mice infected with pneumonia virus of mice (PVM), a mouse pneumovirus that has been used as a model for severe RSV infection in mice. We hypothesized that the Fas/Fas ligand (FasL) system, a dual proapoptotic/proinflammatory system involved in other forms of lung injury, is required for enhanced lung injury i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…This includes a dysregulated recruitment of leukocytes and/or an exaggerated activation of these cells; inappropriate expression of cytokines, lipid mediators, or reactive oxygen species; enhanced activation of death receptor signaling (97,98,140,207,240); or an uncontrolled activity of platelets or the coagulation cascade (154). In general, these responses are initiated and maintained by recognition of danger-or pathogen-associated molecular patterns…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%
See 1 more Smart Citation
“…This includes a dysregulated recruitment of leukocytes and/or an exaggerated activation of these cells; inappropriate expression of cytokines, lipid mediators, or reactive oxygen species; enhanced activation of death receptor signaling (97,98,140,207,240); or an uncontrolled activity of platelets or the coagulation cascade (154). In general, these responses are initiated and maintained by recognition of danger-or pathogen-associated molecular patterns…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%
“…This includes a dysregulated recruitment of leukocytes and/or an exaggerated activation of these cells; inappropriate expression of cytokines, lipid mediators, or reactive oxygen species; enhanced activation of death receptor signaling (97,98,140,207,240); or an uncontrolled activity of platelets or the coagulation cascade (154). In general, these responses are initiated and maintained by recognition of danger-or pathogen-associated molecular patterns (DAMPs/PAMPs) by highly conserved pattern recognition receptors such as TLRs (Toll-like receptors), NLRs (NOD-like receptors), RLRs (RIG-I-like receptors), C-type lectin receptors, and AIM2 (absence in melanoma 2-like) receptors (178,259,260).…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%
“…In addition to increased levels of cytokines in the airways, mechanical ventilation activated caspase-dependent cell death pathways leading to acute lung injury in PVM-infected mice. In a subsequent study, van den Berg and colleagues [83] found that inflammatory injuries associated with mechanical ventilation were less severe in lpr (Fas-deficient) mice although all mice ultimately succumbed to infection.…”
Section: Using the Pvm Model To Explore Human Diseasementioning
confidence: 99%
“…Among the individual cytokines with an impact on the pathogenesis of pneumovirus infection, CCL3 was shown to promote neutrophil recruitment; blockade of CCL3 or its receptor, CCR1, contributes improved survival in response to acute PVM infection (8,9). Other cytokine ligands and receptors implicated in promoting inflammatory pathology in PVM infection include cysteinyl leukotrienes, ChemR23, Fas/FasL, and CD8 + T cell-derived mediators (10)(11)(12)(13).…”
mentioning
confidence: 99%